Resistance status of upland NERICA rice varieties to termite damage in northcentral Nigeria - Agunbiade, T.A.; Nwilene, F.E.; Onasanya, A.; Semon, M.; Togola, A.; Tamo, Manuele; Falola, O.O. (Science Alert, 2009)
Upland rice is mostly at risk from soil insect pests, including termites which cause significant yield losses. Studies were conducted at Kasua-Mangani, Kaduna State, Northcentral Nigeria, to evaluate the resistance status of 18 upland NERICA rice varieties to termite attack. The percent plant attacked by termites on the 18 NERICA varieties at 60 and 90 Days after Sowing (DAS) was between 2.47 to 12.45% and 3.82 to 20.89%, respectively. There was no significant difference in the response of NERICA rice varieties to termite attack at 60 and 90 DAS. The resistance status of NERICA rice varieties to termite attack was classified into 4 groups as follows: Moderately Resistant (MR), Moderately Susceptible with recessive resistance (MSr), Moderately Susceptible (MS) and Highly Susceptible (HS) according to cluster analysis. Of the 18 NERICA rice varieties studied, only NERICA 5, 14 and 18 were classified as MR and could be recommended as the most adapted rice varieties in termite prone areas of Northcentral Nigeria.